Wigeon Anas penelope numbers and bags during two hunting regulation schemes at Skallingen, Denmark - Larsen, Jesper K (Wildfowl, 1996)
A comparison of Wigeon numbers was made during two different temporal hunting regulation schemes at Skallingen in the Danish Wadden Sea. The hunting was conducted on a saltmarsh on which Wigeon fed at night. During 1979-86, a period of three days of hunting alternated with five days without hunting, between 7 September and 30 December. Hunting was allowed in both the morning and evening. During 1987-93, hunting was allowed every day, between 1 October and 20 December, but restricted to evenings only. Coincident with this change in hunting regulations, the October peak in Wigeon numbers failed to appear, and the overall number of bird-days decreased. Flooding frequency could not explain this change in patterns of occurrence. Furthermore, the decrease in Wigeon numbers at Skallingen was in contrast to the trends in the flyway and regional populations. With the change in hunting regulations the overall hunting intensity increased, and an indication was found that the number of Wigeon shot increased as well. The cessation of hunting in September and the increased number of hunting days in November had no apparent effect on Wigeon numbers. Possible reasons for this are discussed. It is concluded that the change in hunting regulations was counter productive to the most important quarry species.